Spontaneous Regression of an Inflammatory Myofibroblastic Tumor: A Case Report and a Review of the Literature - Bianca Medici; Eugenia Caffari; Massimiliano Salati; Andrea Spallanzani; Ingrid Garajova; Federico Piacentini; Massimo Dominici; Fabio Gelsomino (Case Reports in Oncology)
Introduction: Spontaneous tumor regression is the volumetric reduction or complete disappearance of a primary tumor or metastatic sites (single or multiple) without the administration of treatments. This rare phenomenon occurs most commonly in certain types of neoplasms. Case Presentation: In this manuscript, we describe a spontaneous tumor regression in an adult patient followed at the Modena Cancer Center and affected by retroperitoneal inflammatory myofibroblastic tumor, an ultra-rare subtype of sarcoma. Finally, we will provide a concise review of the literature and try to explain the mechanisms underlying the tumor regression described in the clinical case. Conclusion: The etiopathogenetic mechanisms for spontaneous tumor regression are not yet fully understood and likely involve a complex interplay among immunological mechanisms, growth factors, cytokines, and hormonal factors.